A new species of Platyla (Mollusca: Gastropoda: Aciculidae) fills a biogeographic gap in the Mediterranean - Altaba, Cristian R. (Zootaxa, 2013)
The family Aciculidae Woodward, 1854 is endemic to the southwestern Palaearctic and includes tiny operculate land snails living in the soil or underground, and seldom encountered. The genus Platyla Moquin-Tandon, 1856 is restricted to Europe west of the Great and Pannonian Steppes, occurring on islands only in the Ionian Sea off Greece, along the Dalmatian coast of Croatia, and in the Tyrrhenian Sea on Sicily, Sardinia and Elba (Boeters et al. 1989; Cianfanelli et al. 2000; Bodon & Cianfanelli 2008; Subai 2009). Its absence from the Balearic archipelago remained as a puzzling gap, given its palaeogeographic relationship with surrounding land masses. Herein I describe a very rare new species of Platyla from the island of Mallorca, which is most similar to congeners living in Sicily, around the Adriatic and in the Pyrenees, supporting the hypothesis of Neogene vicariance through microplate dispersal in the western Mediterranean.